2013
DOI: 10.1162/jocn_a_00431
|View full text |Cite
|
Sign up to set email alerts
|

Visual–Motor Interactions during Action Observation Are Shaped by Cognitive Context

Abstract: Abstract■ Interactions between the visual system and the motor system during action observation are important for functions such as imitation and action understanding. Here, we asked whether such processes might be influenced by the cognitive context in which actions are performed. We recorded ERPs in a delayed go/no-go task known to induce bidirectional interference between the motor system and the visual system (visuomotor interference). Static images of hand gestures were presented as go stimuli after parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…This modulation might be more likely to emerge during precision grips as this movement is sensitive to high-level cognitive manipulations2728. The analysis of kinematics allowed us to: i) monitor participants' behaviour during the interaction and verify they were on-line adapting to the avatar's movements, thus validating human-avatar interactions as reliable set-ups to simulate human-human joint actions in a controlled environment; ii) measure visuo-motor interference effects through direct investigation of motor behaviour, thus expanding influential studies373839 based on inferences derived from the analysis of response times.…”
mentioning
confidence: 99%
“…This modulation might be more likely to emerge during precision grips as this movement is sensitive to high-level cognitive manipulations2728. The analysis of kinematics allowed us to: i) monitor participants' behaviour during the interaction and verify they were on-line adapting to the avatar's movements, thus validating human-avatar interactions as reliable set-ups to simulate human-human joint actions in a controlled environment; ii) measure visuo-motor interference effects through direct investigation of motor behaviour, thus expanding influential studies373839 based on inferences derived from the analysis of response times.…”
mentioning
confidence: 99%
“…Social modulations of observing a motion sequence on-screen depicting an irrelevant yet (in-)compatible action are documented for the automatic imitation task (Brass et al, 2001 ; Butler et al, 2016 ; Cracco, Genschow, et al, 2018b ; for an overview, see Cracco et al, 2018a , b ). For instance, individuals imitate others less strongly when they observe actions from a third-person perspective compared with a first-person perspective (Bortoletto et al, 2013 ; Genschow et al, 2013 ; Lamm et al, 2007 ; Vogt et al, 2003 ) or when they face out-group compared with in-group members (Genschow & Schindler, 2016 ; but see Genschow, Westfal, et al, 2021b , for a failed replication of this finding). Similarly, joint Simon effects emerge for situations in which participants believe to observe the action of a human interaction partner seated in an adjacent cubicle (Tsai et al, 2008 ).…”
mentioning
confidence: 99%
“…The congruency effect during action preparation was significant over central motor areas, while the congruency effect during action initiation was significant over right frontal sensors. Bortoletto et al (2013) reported greater ERP amplitudes for congruent versus incongruent actions during action initiation; however, their analysis focused on the 170ms time point. Field intensity values on Figure 5.4 also suggest similar albeit non-significant trends in left occipital regions during action preparation, and at central and frontal regions during action initiation.…”
Section: Congruency Effectmentioning
confidence: 93%
“…One explanation for these divergent findings is that attentional focus and the relative timing of the observed actions relative to planned or executed actions can modulate early visual responses to the observed actions (Bortoletto et al, 2011(Bortoletto et al, , 2013. In a study by Bortoletto et al (2011), images of congruent or incongruent gestures were presented on the screen while participants were waiting for a "go" cue to initiate an already planned gesture.…”
Section: Concurrent Action Production and Observationmentioning
confidence: 99%
See 1 more Smart Citation